Diversity, biomass, and trophic structure of a central Amazonian rainforest bird community - Johnson, Erik I.; Stouffer, Philip C.; Vargas, Claudeir Ferreira (Revista Brasileira de Ornitologia, 2011)
Amazonian forest bird communities are among the richest in the world. Even so, relatively little is known about the organization of the entire avian community at local scales or about differences across Amazonia. These are fundamental data not only for understanding the processes generating and maintaining tropical diversity, but also as a baseline for evaluating anthropogenic changes to Amazonian forests. Here we provide a description of the entire bird community for a 100 ha plot of terra firme forest at the Biological Dynamics of Forest Fragments Project, near Manaus, Brazil, based on spot-map and mist net surveys augmented by additional field and analytical techniques. Although our results are from a single plot surveyed in a single year, our methods and interpretation reflect nearly 30 years of ornithological research at the site. We found 228 species on the plot, of which 207 were considered part of the core regional avifauna. Median density was five individuals/100 ha. Only 13 species (6% of the core species) had densities ≥ 20 individuals on the plot, although 55 species (27%) had ≤ 2 individuals. No species had territories smaller than 3 ha; median territory size was 11 ha for the 103 species for which we could make reasonable estimates. Measured by numbers of species or individuals, the plot was dominated by insectivores (54% of species, 62% of individuals). Biomass, however, was dominated by frugivores and granivores (59%). Compared to available data from other Amazonian forests, our site appears to have comparable richness of a similar set of species, but lower density and greater patchiness. Our results suggest that the area required to support populations of many species will be even greater in central Amazonia than in western Amazonia.
Diversidade, biomassa, e estrutura trófica de uma comunidade de aves de floresta tropical na Amazônia central
Keywords: Anthropogenic Effect; Avifauna; Biomass; Community Composition; Dominance; Forest Dynamics; Frugivory; Granivory; Insectivore; Ornithology; Patchiness; Population Density; Rainforest; Range Size; Species Diversity; Species Richness; Trophic Structure; Amazonia; Aves